Abraham Lincoln, philosopher statesman - Fornieri, Joseph R. (Southern Illinois University Press, 2014)
Providing an accessible framework for understanding Lincoln's statesmanship, this thoughtful study examines the sixteenth president's political leadership in terms of the traditional moral vision of statecraft as understood by epic political philosophers such as Aristotle and St. Thomas Aquinas. Fornieri contends that Lincoln's character is best understood in terms of Aquinas's understanding of magnanimity or greatness of soul, the crowning virtue of statesmanship. True political greatness, as embodied by Lincoln, involves both humility and sacrificial service for the common good. The enduring wisdom and timeless teachings of these great thinkers, Fornieri shows, can lead to a deeper appreciation of statesmanship and of its embodiment in Abraham Lincoln.